Diagnostic value of Xpert® Bladder Cancer Monitor in the follow-up of patients affected by non-muscle invasive bladder cancer: an update. (March 2021) - D'Elia, Carolina; Folchini, Decio M.; Mian, Christine; Hanspeter, Esther; Schwienbacher, Christine; Spedicato, Giorgio Alfredo; Pycha, Stefan; Vjaters, Egils; Degener, Stephan; Kafka, Mona; Pycha, Armin; Trenti, Emanuela
Aims: Xpert ® Bladder Cancer Monitor is a urinary marker based on the evaluation of five target mRNAs overexpressed in patients with bladder cancer (BC). The aim of our study is to update our results regarding the diagnostic accuracy of the Xpert ® Bladder Cancer Monitor test in the follow-up of patients with non-muscle invasive bladder cancer (NMIBC). Methods: We conducted a prospective study on 1015 samples of 416 patients (mean age 72.2 ± 10.3 years) under follow-up for NMIBC. Patients underwent voided urinary cytology, the Xpert ® Bladder Cancer Monitor test and cystoscopy and, if positive, a transurethral resection of the bladder. Xpert ® Bladder Cancer Monitor was reported as negative or positive: cut-off total Linear Discriminant Analysis (LDA) = 0.5. Results: We identified 168 recurrent tumours: 126 (75%) were low-grade (LG) and 42 (25%) high-grade (HG). Overall sensitivity was 17.9% for cytology, 52.4% for Xpert ® Bladder Cancer Monitor and 54.2% for the two tests combined. The sensitivity of cytology increased from 6.3% in LG to 52.4% in HG tumours whereas Xpert ® Bladder Cancer Monitor showed a sensitivity ranging from 42.9% in LG to 80.9% in HG tumours. Combined cytology and Xpert ® Bladder Cancer Monitor yielded an overall sensitivity of 45.2% for LG and 80.9% for HG tumours. Overall specificity was 98.5% for cytology and 78.4% for Xpert ® Bladder Cancer Monitor and 78.2% for the two tests combined. The area under the curve (AUC) for Xpert ® Bladder Cancer Monitor was 0.71; stratifying the patients according to the European Association of Urology risk groups, the AUC was 0.69, 0.67 and 0.85 for low, intermediate and high risk, respectively ( p  = 0.0003). Conclusion: Our data confirm a significantly higher sensitivity of Xpert ® Bladder Cancer Monitor than for cytology in a larger patient cohort. The test performed very well in terms of specificity but could not reach the high value of cytology. Along with voided urinary cytology the test could allow to reduce cystoscopies in follow-up patients, reducing discomfort to the patients and costs.